2020
DOI: 10.17478/jegys.702884
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical understanding and reasoning of vocational school students in agriculture-based mathematical tasks

Abstract: Mathematical understanding and reasoning are important in solving agriculture problems. This research aims to describe students' mathematical understanding and reasoning in agriculture-based mathematical tasks. This mathematical task corresponds to the competency of students' expertise to minimize the gap between mathematics learned at school and the workplace. This research used a descriptive case study method. Participants are students of the vocational crops and horticulture agribusiness of 11th graders stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…1, a review of the evidence of the test response was then conducted because one of the important things in selection fairness is equality in the questions the participants are working on [43], [44]. Recent study also showed that students' assessment result was influenced by the design of tasks and students' experiences especially in mathematics subject [45]. Therefore, participant responses were analyzed based on correctness index, which were compared with the set of questions worked out by participants as shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…1, a review of the evidence of the test response was then conducted because one of the important things in selection fairness is equality in the questions the participants are working on [43], [44]. Recent study also showed that students' assessment result was influenced by the design of tasks and students' experiences especially in mathematics subject [45]. Therefore, participant responses were analyzed based on correctness index, which were compared with the set of questions worked out by participants as shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Bakker (2014), in regard to this, highlights the importance of mathematics learning in vocational schools and its relevance to students' future work and profession, or its utility for vocational practices to develop student's mathematics knowledge to meet the vocational needs. In other words, mathematics learning activity in vocational schools should be designed in such a way that reflects vocational culture or environment, provides a positive impact on students' engagement in mathematics learning (Dalby & Noyes, 2015), is useful for students to deal with various problems in their future workplace (Fatimah & Prabawanto, 2020). Students' opinions towards mathematics' relevance to art would appear as one of the interesting themes appearing in this research.…”
Section: Discussionmentioning
confidence: 95%
“…It is in line with the research results of Fatimah et al (2019), which states that agricultural vocational students who are given problems in horticultural agribusiness help students reasoning in solving tasks. The context of the task by students' experience and knowledge supports students' mathematical reasoning (Fatimah & Prabawanto, 2020;Khoeriyah & Ahmad, 2020). It is clear that the task's context according to the student's environment affects reasoning in completing a task.…”
Section: Lcmentioning
confidence: 99%